(6x-1)/5- 2x/3=3
multiply 15 to each number
3(6x-1) - 5(2x) = 3(15)
18x - 3 - 10x = 45
8x = 45 + 3
8x = 48
x = 48/8
x = 6
2007-08-10 17:31:11
·
answer #1
·
answered by wow 2
·
0⤊
0⤋
(6x-1)/5-2x/3=3 Multiple both sides by 3 =
3(6x-1)/5- 2x=9 Multiple both sides by 5=
3(6x-1)-10x=45 solve for X =
18x-3-10x=45
18x-10x=48
8x=48
x=6
Plug 6 into the equation you get
6(6)-1/5-2(6)/3=3 =
36-1/5 - 12/3= 3 =
35/5 -12/3=3 =
7-4=3 =
3=3
2007-08-10 18:01:11
·
answer #2
·
answered by Sharkboy 1
·
0⤊
0⤋
step 1: first find a common denominator (for simplicity, use 15).
step 2: multiply by the common denominator.
15 {(6x-1)/5- 2x/3=3} becomes [3*(6x-1)] - [5*(2x)] = 15*3 which turns into 18x - 3 - 10x = 45
step 3: combine like terms by adding 3 to both sides.
18x - 3 - 10x +3 = 45 + 3 becomes 18x - 10x = 45 + 3 which turns into 8x = 48
step 4: solve for x by dividing each side by 8.
8x / 8 = 48 /8 becomes x = 6
to check
step 1: substitute 6 wherever x appears, into the original problem.
(6x-1)/5- 2x/3=3 becomes [(6*6) - 1]/5 - (2*6)/3 = 3
and u get that (36-1)/5 - 12/3 = 3
step 2: 35/5 - 12/3 = 3
step 3: 7 - 4 = 3
step 4: 3 = 3
therefore, x = 6 is the answer
2007-08-10 17:41:30
·
answer #3
·
answered by pillows 1
·
0⤊
0⤋
How I would go about solving this problem would be to get rid of the fractions, even though I love them (yeah. I'm weird). To get rid of them, you need to multiply the whole equation by both of the denominators (5 and 3), to save a step, I'm going to multiply through by both of them at the same time, the 5's will cancel out in the first fraction and the 3's in the second leaving you with:
3(6x-1) -5(2x) =3*5*3 now simplify it (multiply)
18x-3 -10x = 45 combine like terms:
8x - 3 = 45 add 3 to both sides:
8x = 48 divide through by 8 to find the value of x:
x=6
to check it, plug 6 in for x in the original equation:
(6*6-1)/5 - 2(6)/3 = 3
(36-1)/5 - 12/3 = 3
35/5 - 4 = 3
7 - 4=3
3=3 it checks =)
2007-08-10 17:33:20
·
answer #4
·
answered by sarajschryver 2
·
0⤊
0⤋
so 6x/5 - 1/5 -2x/3 = 3
get everything over a common denominator (15)
18x/15 - 3/15 - 10x/15 = 45/15
8x/15 = 48/15
8x = 48
x = 6
then replace x with 6 in the original equation and if it is correct then u hav the rite answer.
(6x6 - 1)/5 - 2x6/3 = 3
35/5 - 12/3 =3
7 - 4 = 3
which it does so RHS = LHS so the answer x=6 is correct!
2007-08-10 17:30:15
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
3(6x - 1) - 10x = 45
18x - 3 - 10x = 45
8x = 48
x = 6
Check
(36 - 1) / 5 - 12 / 3 = 7 - 4 = 3 (as required)
2007-08-10 19:50:59
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
you multiply both sides by 5*3 =15
3*(6x-1)-10x=45
18x-3-10x=45
8x=48
x=6
and replacing x by 6 check below
(36-1)/5-12/3=7-4=3
2007-08-10 17:33:43
·
answer #7
·
answered by maussy 7
·
0⤊
0⤋
(6x-1)/5- 2x/3=3
3(6x-1) - 5(2x) = 15(3)
18x - 3 - 10x = 45
8x = 48
x = 6
2007-08-10 17:46:55
·
answer #8
·
answered by vlee1225 6
·
0⤊
0⤋
first of all, divide the two components by way of -3. x=-9 you could verify by way of plugging -9 back into the equation for x to verify if it extremely does artwork. -9 x -3 = 27. subsequently, -9 is the right fee for x.
2016-11-12 00:20:57
·
answer #9
·
answered by ? 4
·
0⤊
0⤋
x=6;and it verifies the answer
2007-08-10 17:56:41
·
answer #10
·
answered by Zinda 1
·
0⤊
0⤋